Antioxidant and Anti-Inflammatory Effects of Rhei Rhizoma and Coptidis Rhizoma Mixture on Reflux Esophagitis in Rats. (27th April 2016) - Kwon, O Jun; Kim, Min Yeong; Shin, Sung Ho; Lee, Ah Reum; Lee, Joo Young; Seo, Bu-il; Shin, Mi-Rae; Choi, Hyun Gyu; Kim, Jeong Ah; Min, Byung Sun; Kim, Gyo-Nam; Noh, Jeong Sook; et al.
Abstract : The purpose of this study was to investigate the antioxidant and anti-inflammatory effects of the combined extract of Rhei rhizoma and Coptidis rhizoma (RC-mix) in experimental model of acute reflux esophagitis. The antioxidant activity was assessed by in vitro 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assays. RC-mix was given at 100, 200, and 400 mg/kg body weight 2 h prior to induction of reflux esophagitis (RE). After 5 h, the effects of RC-mix treated rats were compared with those of normal and control rats. The representative flavonoid contents of RC-mix, such as sennoside A, epiberberine, coptisine, palmatine, and berberine, were detected using HPLC. The elevated esophageal mucosa damage was markedly ameliorated by RC-mix treatment in a dose-dependent manner. Furthermore, the administration of RC-mix reduced the increase of serum reactive oxygen species (ROS) and peroxynitrite (ONOO − ). The improvement of superoxide dismutase (SOD) and heme oxygenase-1 (HO-1) levels were marked in the group given RC-mix. Moreover, the elevation of inflammatory mediators and cytokines by nuclear factor-kappa B (NF-κ B) activation in control rats decreased by RC-mix pretreatment. These results indicate that RC-mix treatment reduces the pathological states of esophagitis via regulating NF-κ B mediated inflammation related to oxidative stress.